Polyphenols: Chemoprevention and therapeutic potentials in hematological malignancies - Izuegbuna, Ogochukwu O. (Frontiers in Nutrition, 2022)
Polyphenols are one of the largest plant-derived natural products and they play an important role in plants' defense as well as in human health and disease. A number of them are pleiotropic molecules and have been shown to regulate signaling pathways, immune response and cell growth and proliferation which all play a role in cancer development. Hematological malignancies, on the other hand, are cancers of the blood. While current therapies are efficacious, they are usually expensive and with unwanted side effects. Polyphenols have been reported to cause cell cycle arrest, and induce apoptosis via multiple mechanisms. They also have immunomodulatory activities where they enhance T cell activation and suppress regulatory T cells. They carry out these actions through such pathways as PI3K/Akt/mTOR and the kynurenine. They can also reverse cancer resistance to chemotherapy agents. In this review, I look at some of the molecular mechanisms of action of polyphenols and their potential roles as therapeutic agents in hematological malignancies. Here I discuss their anti-proliferative and anti-neoplastic activities especially their abilities to induce apoptosis and autophagy in hematological malignancies. I also looked at clinical studies done mainly in the last ten to fifteen years on various polyphenol combinations and how they enhance synergism. I recommend that further preclinical and clinical studies be carried out to ensure safety and efficacy before polyphenol therapies are officially moved to the clinics.